Exploring the implications of blocking renin-angiotensin-aldosterone system and fibroblast growth factor 23 in early left ventricular hypertrophy without chronic kidney disease - Kentaro Watanabe; Hideki Fujii; Kohei Okamoto; Keiji Kono; Shunsuke Goto; Shinichi Nishi (Frontiers in Endocrinology, 2023)
BackgroundWhether fibroblast growth factor 23 (FGF23) directly induces left ventricular hypertrophy (LVH) remains controversial. Recent studies showed an association between FGF23 and the renin-angiotensin-aldosterone system (RAAS). The aim of this study was to investigate changes in FGF23 levels and RAAS parameters and their influences on LVH.MethodsIn the first experiment, male C57BL/6J mice were divided into sham and transverse aortic constriction (TAC) groups. The TAC group underwent TAC at 8 weeks of age. At 1, 2, 3, and 4 weeks after TAC, the mice were sacrificed, and blood and urine samples were obtained. Cardiac expressions of FGF23 and RAAS-related factors were evaluated, and cardiac histological analyses were performed. In the second experiment, the sham and TAC groups were treated with vehicle, angiotensin-converting enzyme (ACE) inhibitor, or FGF receptor 4 (FGFR4) inhibitor and then evaluated in the same way as in the first experiment.ResultsIn the early stage of LVH without chronic kidney disease, serum FGF23 levels did not change but cardiac FGF23 expression significantly increased along with LVH progression. Moreover, serum aldosterone and cardiac ACE levels were significantly elevated, and cardiac ACE2 levels were significantly decreased. ACE inhibitor did not change serum FGF23 levels but significantly decreased cardiac FGF23 levels with improvements in LVH and RAAS-related factors, while FGFR4 inhibitor did not change the values.ConclusionsNot serum FGF23 but cardiac FGF23 levels and RAAS parameters significantly changed in the early stage of LVH without chronic kidney disease. RAAS blockade might be more crucial than FGF23 blockade for preventing LVH progression in this condition.